По поводу интерпретации памятников Маячного полуострова - Зубарь, В.М.; Буйских, А.В. (Материалы по археологии, истории и этнографии Таврии, 2006)
Целью настоящей статьи является попытка пересмотреть некоторые сделанные ранее выводы, а также высказать авторскую точку зрения на вопросы интерпретации памятников ближайшей округи Херсонеса. Основное внимание будет уделено хронологии памятников, поскольку до сих пор проблема времени возникновения поселений на Маячном полуострове и у Карантинной бухты остается все еще дискуссионной. The paper is devoted to the critical analysis of the archaeological sites on Majacnyj Peninsula (Lighthouse Point). Upon reconsidering the new dating of the foundation of the settlement proposed by A. N. Sceglov - the end of the 6"' century BC., it was suggested to return to the previous dating lying within the first half of the 4*·^ c. BC. Thus, the starting point of defensive system construction at the isthmus and the appearance of the houses between the walls, as well the early farmhouses on the territory of the Majacnyj Peninsula, were synchronized with the building activity in Chersonesos itself, its inner land division and construction of city fortifications. Following this a new interpretation of the Majacnyj Peninsula archaeological sites was proposed - a settlement and a place of farming activity of the new wave of population coming from metropolis - epoikoi. It was proposed to attribute the buildings excavated on the fortified isthmus as a fortified urban settlement rather than a city. So, the term Strabo’s Old Chersonesos reflects not an earlier settlement on the Majacnyj Peninsula, but the stages of development of the new farming lands on the Herakleian Peninsula as a whole.